2017
DOI: 10.1053/j.gastro.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nuclear Factor−κB by Tumor Necrosis Factor in Intestinal Epithelial Cells and Mouse Intestinal Epithelia Reduces Expression of the Chloride Transporter SLC26A3

Abstract: Background & Aims Diarrhea associated with inflammatory bowel diseases (IBD) has been associated with increased levels of inflammatory cytokines, including tumor necrosis factor (TNF). The intestinal mucosa of patients with IBD has reduced expression of solute carrier family 26 member 3 (SLC26A3, also called DRA). We investigated whether TNF directly affects expression of DRA in human intestinal epithelial cells (IECs) and in intestines of mice, and studied the mechanisms of these effects. Methods We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…We observed that mutation (−1137 to −1128 bp) of the DRA promoter region disrupted the TNF-α-induced reduction in DRA-LUC activity compared with the WT control, suggesting that the TNF-α-induced inhibition of DRA promoter activity is mediated by NF-кB. Our finding is consistent with a recent study by Kumar et al, who also showed that TNF-α decreases DRA expression by activating NF-кB [43]. There are indirect signaling pathways between TNF-α and DRA.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that mutation (−1137 to −1128 bp) of the DRA promoter region disrupted the TNF-α-induced reduction in DRA-LUC activity compared with the WT control, suggesting that the TNF-α-induced inhibition of DRA promoter activity is mediated by NF-кB. Our finding is consistent with a recent study by Kumar et al, who also showed that TNF-α decreases DRA expression by activating NF-кB [43]. There are indirect signaling pathways between TNF-α and DRA.…”
Section: Discussionsupporting
confidence: 92%
“…26-29 Its molecular size as revealed by Western blot varies and this is probably due to heterogenous glycosylation in different cell systems and animal species. 26-30 We report here that human DRA in HEK293/DRA cells, Caco-2 cells and differentiated proximal colonoids appears as two bands; the upper band is slightly above 102 kDa and the lower band is slightly above 76 kDa, and as previously demonstrated, both of these bands are glycosylated. 19 While the distribution of DRA throughout the human GI tract both horizontally and vertically has been described and there is no debate that it functions as a Cl - /HCO 3 - exchanger with 1:1 stoichiometry, there continues to be confusion relating to its acute regulation, particularly in digestive physiology and in the pathophysiology of cAMP-driven secretory diarrheal diseases.…”
Section: Discussionsupporting
confidence: 82%
“…Lipophilicity of VX-770 Affects F508del-CFTR Stability reduce SLC26A3 expression through direct binding to NF-kB (Kumar et al, 2017). Hence, it is possible that the destabilizing effect of VX-770 that we observed on SLC26A3 may modify the ORKAMBI response in the intestinal tissues.…”
Section: Discussionmentioning
confidence: 83%